Chapter Medieval Endowment Cultures in Western India: Buddhist and Muslim Encounters - Some Preliminary Observations - Schmiedchen, Annette (Welten Süd- und Zentralasiens / Worlds of South and Inner Asia / Mondes de l'Asie du Sud et de l'Asie Centrale, 2019)
The volume analyses the encounter between Buddhist and Muslim communities in South and Central Asia during the medieval period. The articles by historians, epigraphists, philologists, art historians and archaeologists provoke a fresh look at relevant sources, focusing on the areas: deconstructing scholarship on Buddhist/Muslim interactions, cultural and religious exchanges, perceptions of the other, transmission of knowledge, trade and economics.